Desain dan implementasi Arus Keluaran Zeta Penaik-Penurun Inverter Jembatan-H menggunakan STM32F407VET6 - Jonathan Wijaya; Leonardus Heru Pratomo (JURNAL INFOTEL, 2024)
The development of electrical power conversion equipment is increasing, along with the utilization of new and renewable energy sources. Power conversion equipment from DC to AC voltage, known as inverters, is extensively researched and implemented in this sector. These inverters commonly operate as step-down voltage in specific applications used as step-ups with limited operating ranges. A step-up-down inverter with a single power circuit is developed to overcome this issue. Still, the number of power switches used correlates with the complexity of its control strategy. This paper investigates a step-up-down inverter using the Zeta H-Bridge Inverter with the implementation of six power switches. Furthermore, this type of inverter is operated with a controlled output current utilizing the STM32VET407 microcontroller. The control method is derived based on possible operational modes. An HX10-P current sensor detects the output current. It maintains itself according to the current reference by installing a proportional-integral controller. The initial verification utilizes computational simulation with power simulator software, ensuring the system operates as intended. The final stage involves implementation in the laboratory and testing with standardized equipment. The test results meet the IEEE 519 standard, where the output current has a THD of 1.1%.